Diagnosing Small for Gestational Age during second trimester routine screening: Early sonographic clues - Erdem Fatihoglu; Sonay Aydin (Elsevier, 2020)
Objective: Small for gestational age (SGA) is generally defined as birth weight being at or below the 10th percentile. Children with SGA have a higher risk for complications. There is a need for early predictors, as the accurate diagnosis rate is only 50%. In the current study, we aimed to evaluate diagnostic performance of ultrasound (US)/color Doppler ultrasound (CDUS) parameters (umbilical vein-UV, right portal vein-RPV diameter/flow rate, and portal sinus-PS diameter) examined at 20-22 gestational week as SGA diagnostic factors. Materials and methods: 93 pregnant included (32 SGA, 61 controls). All the US examinations were performed between 20 and 22 weeks of gestation. UV, RPV, and PS measurements were performed by using the same image acquired for abdominal circumference measurement. A fetus with as estimated fetal weight (EFW) below the 10th percentile was diagnosed as SGA and SGA at birth was defined as having a birth weight under the 10th percentile. Results: Pregnant women in the SGA group were significantly older (30 ± 4.8 vs. 26.6 ± 5.4 years, p < 0.01). Median UV diameter was significantly lower in SGA group (2.20 vs. 2.40 mm, p = 0.001). Median RPV diameter was significantly lower in SGA group (2 vs. 2.10 mm, p = 0.018). Median PS diameter was significantly lower in SGA group (2 vs. 20.10 mm, p = 0.008). Conclusion: UV, RPV, and PS diameters can be earlier predictors for SGA diagnosis. Routinely evaluation of these parameters during second trimester screening can increase SGA diagnosis rates and serve for early diagnose. Keywords: Umbilical vein, Portal sinus, Right portal vein, SGA